Pandangan Hukum Islam terhadap Penyalahgunaan Napza pada Anak di Bawah Umur - Ahmad Ropei (Mutawasith: Jurnal Hukum Islam, 2020)
This study aims to reveal positive legal and Islamic law arrangements against legal sanctions on the abuse of Narcotics, Psychotropics and Addictive Substances (Drugs) by minors. The method used in this research is content analysis (content analysis). The type of data used is qualitative data. The data collection technique used is by means of literature. The results showed that drug abuse committed by minors is regulated in Article 128 paragraph (2) of Law No. 35 of 2009 which states that a child who commits drug abuse cannot be prosecuted. Apart from that, Article 45 also states that a child cannot be prosecuted until he reaches adulthood. Meanwhile, parents of children who are drug abusers are obliged to report to the relevant authorities in order to receive treatment and / or treatment through medical rehabilitation and social rehabilitation. From the point of view of Islamic law, drug abuse committed by minors cannot be punished. This is because minors cannot be held responsible for the crime because they have not been subject to legal imposition (khitob) or because they have not reached aqil-baligh.